Empowerment of Local Snack Product Development for Farmers - Fitri Anugrasari (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
This essay uses the example of Palopo in South Sulawesi to discuss the value of empowering small-scale producers to develop new types of refreshing beverages using only locally sourced ingredients. We begin by talking about the challenges faced by small-scale manufacturers and how innovation can aid them. Then, we dive into the Palopo case study, which centers on the work of the Palopo Food Entrepreneurship Network (JAWIKA) to aid farmers and other makers in creating high-quality beverages. As a consequence of this initiative, producers have seen an increase in revenue, new jobs have been created, and cultural traditions have been protected. Additionally, the article provides both lessons learned and suggestions for similar initiatives that could be implemented in other remote areas, emphasizing the importance of market research, access to resources and infrastructure, training and support. Collaboration and networking between producers, researchers, and marketing pros is crucial to the success of any undertaking. Supporting economic growth and preserving cultural traditions in outlying areas through the empowerment of local producers through the development of locally made snacks is, in general, an effective strategy.